2018
DOI: 10.1111/myc.12815
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic cut‐off of Aspergillus fumigatus‐specific IgG in the diagnosis of chronic pulmonary aspergillosis

Abstract: Aspergillus fumigatus-specific IgG is pivotal in making the diagnosis of chronic pulmonary aspergillosis (CPA). However, the cut-off value for A. fumigatus-specific IgG remains unknown. We included consecutive treatment-naïve subjects with chronic cavitary pulmonary aspergillosis (CCPA, cases). The controls were subjects with treated pulmonary tuberculosis, who had residual radiological abnormality and minimal symptoms. The diagnosis of CCPA was based on consistent clinicoradiological features along with demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(109 citation statements)
references
References 21 publications
3
103
1
2
Order By: Relevance
“…In the current study, A fumigatus ‐specific IgG had a moderate sensitivity but excellent specificity for diagnosing SA. Although the cut‐off value is similar to that used in other forms of chronic aspergillosis (CCPA and ABPA), the lower sensitivity is possibly due to the saprophytic nature of the infection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, A fumigatus ‐specific IgG had a moderate sensitivity but excellent specificity for diagnosing SA. Although the cut‐off value is similar to that used in other forms of chronic aspergillosis (CCPA and ABPA), the lower sensitivity is possibly due to the saprophytic nature of the infection …”
Section: Discussionmentioning
confidence: 99%
“…The Institute Ethics Committee approved the study protocol, and a written informed consent was obtained from all the study participants. Some of the data have been previously published …”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the included studies are presented in S1Table. The earliest study was published in 1983 [22] and the five most current articles were published in 2015 [23], 2016 [24, 25, 26] and 2018 [27]. Nine studies took place in five countries: Japan [25, 28], Brazil [23], United Kingdom [24, 29], France [26, 30, 31] and India [27], but in 4 articles, the study countries were not reported [22, 32, 33, 34].…”
Section: Resultsmentioning
confidence: 99%
“…Nine articles presented DID as the reference test [22, 23, 25, 27, 28, 30, 32, 33, 34]; an article presented two reference tests, DID and CIE [34] and four studies presented only CIE as the reference test [24, 26, 29, 31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation